Analysis of Auction Efficiency and Effectiveness PNBP at Batam - Gusma Maulana; Puspita Rama Nopiana; Yohan Fitriadi (International Journal of Integrative Sciences, 2023)
All parties related to the running of the auction, both the buyer and the seller, know that the auction is beneficial to the Indonesian economy. The method used is descriptive analysis. The partial test results explain that the auction efficiency variable has a positive and significant effect on PNBP. This means that the implementation of the auction at the Batam KPKNL has a small burden of carrying out the auction compared to the results obtained in the form of non-tax state revenue. Furthermore, it also explains that the auction effectiveness variable affects PNBP. This means that the Batam KPKNL always achieves satisfactory targets every year, and it needs to be a concern of management so that it can always achieve the target. The simultaneous test results explain that the variable efficiency and auction effectiveness simultaneously affect PNBP. This means that the implementation of the auction at the Batam KPKNL has a small burden of carrying out the auction compared to the results obtained in the form of non-tax state revenue. And the Batam KPKNL always achieves satisfactory targets every year